Proposta de modelo gerencial de custo: um estudo de caso na Faculdade de Tecnologia da Universidade Federal do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
This paper aims to present and implement a cost management model as a tool to support the Faculty of Technology, Federal University of Amazonas (FT/UFAM). The research objective was to show the cost per student enrolled in methods of teaching undergraduate and graduate in 2010 through a case study, based on the method of "absorption costing" showing the values of direct and indirect costs of period which will enable information organized, identified with their respective origins, application and disposal costs by type of education. From this, we proceeded to calculate the costs of the Academic Unit and subsequently the calculation of the cost of the education service, with the main parameters the direct and indirect costs and the number of students enrolled in the period. Among the 1862 students that they conducted registration were 89.85% and 10.15% in graduation in graduate school and the total cost per student enrolled for the period which corresponded respectively an average of R and R$ 5,234.71 to R$ 5,324.49 year and month respectively on average R$ 436.22 and R$ 436.20. The study also found that the calculated total costs accounted for 79.71% in direct labor, material consumption 0.52%, 4.19% electric power, telephone 0.24%, 0.47% acquisition of books, 7.35% indirect labor, depreciation 6.94% and 1.11% in overall maintenance of the building. The costing methodology developed can contribute to the efficient use of resources by the Academic Unit, and it was possible to see some points that justify the complexity in determining costs in universities.
Keywords: Custo; Modelo gerencial de custos; Custeio por absorção; UFAM; FT; Cost; Model management cost; Absorption costing; UFAM; FT; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO